Risk Factors for Recurrent Tracheoesophageal Fistula After Gross Type C Esophageal Atresia Repair - Yang, Shen; Li, Siqi; Yang, Zhi; Liao, Junmin; Hua, Kaiyun; Zhang, Yanan; Zhao, Yong; Gu, Yichao; Li, Shuangshuang; Huang, Jinshi (Frontiers in Pediatrics, 2021)
Background: To determine the possible risk factors of recurrent tracheoesophageal fistula (rTEF) after Gross type C esophageal atresia (EA) and tracheoesophageal fistula (TEF) repair. Methods: The medical records of 343 pediatric patients with Gross type C EA/TEF who underwent surgical repair were retrospectively analyzed. The patients were retrospectively divided into two groups according to whether they had rTEF. Univariate and multivariable logistic regression analysis were performed to identify risk factors for rTEF. Results: After the diagnosis of EA/TEF, 343 patients (221 boys) underwent primary repairs after birth. According to the follow-up results (257 patients survived, 42 died, and 43 were lost to follow-up), 259 patients (257 survived and two died after rTEF repair) were included in the analysis. rTEF occurred in 33 patients (33/259, 12.74%), with a median onset time to recurrence of 3.8 (2.2, 8.2) months. Multivariate analysis showed that closing the original TEF with ligation and hospital stay ≥ 28.5 days were significant risk factors of rTEF with OR of 4.083 (1.481, 11.261) and 3.228 (1.431, 7.282). Conclusions: Surgical closure technique of original TEF and the length of initial stay could influence the occurrence of rTEF after Gross type C EA/TEF repair.